Physicochemical Characteristics of Titania Particles Synthesized with Gelatin as a Template Before and After Regeneration and Their Performance in Photocatalytic Methylene Blue - Ulfa, Maria; Pangestuti, Indriyani; Anggreani, Cindy Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
TiO2 material has an important position in the processing of methylene blue waste because it is economical, has abundant polymorphs, high sustainability and supports green chemistry applications. Mesoporous TiO2 is a porous material that has higher effectiveness than other TiO2 because the pore structure has a large diameter at the nano scale (2-50 nm) with a regular shape so that the surface area and pore volume are greater than the average for other TiO2. The synthesis of mesopore TiO2 material has so far used the sol-gel route with synthetic pore directing agents such as P123 which can be replaced with gelatin as a cheaper and safer pore directing agent with high sustainability and abundance. Based on the description above, this research aims to photodegrade methylene blue using mesoporous TiO2 (m-TiO2) nanoparticles which were prepared by the sol–gel method using gelatin and P123 as template. X-ray diffraction (XRD), scanning electron microscopy (SEM), Electron dispersive X-Ray (EDX), and UV–vis spectroscopy techniques were used to characterize the samples. Photocatalytic activities of samples for methylene blue degradation were investigated. The catalyst before and after regeneration will be studied so that the effect of regeneration on the results of methylene blue photocatalysis with m-TiO2 can be determined. XRD results confirmed the formation of the anatase and rutile phase for the TiO2 nanoparticles, with crystallite sizes larger after regeneration in the range of 9–21 nm. The large particle size was after regeneration due to the promotion by high temperature treatment. TiO2 nanoparticles showed the best photocatalytic activity on the first use to 91% and remained stable after four cycles with photodegradation efficiency up to 76% based on the measured UV-Vis spectroscopy. TiO2 as synthesis could be the best candidate for catalyst with the high performance after multicycle regeneration. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).